2019
DOI: 10.1002/14651858.cd012668.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for treating urinary incontinence in women

Abstract: Analysis 1.4. Comparison 1 Yoga versus no specific active intervention, Outcome 4 Number of micturitions (daily)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…2 Exercícios que possam fortalecer o core e os MPP, como Pilates e Yoga, têm sido explorados como potenciais alternativas, mas os dados ainda são insuficientes. [47][48][49][50] De facto, Bø et al já tinha reportado uma taxa de IU nas professoras destas modalidades semelhante à da população geral, ainda que a maioria das participantes neste estudo praticava outras modalidades em simultâneo. 51 Num trabalho de 2018, a autora em conjunto com Kruger et al, concluiu que os MPP apenas contraiam 30% a 50% de uma contração em contexto de PFMT, durante a ativação de outros grupos musculares (como abdominais e glúteos), pelo que se questiona a eficácia terapêutica e o impacto que as co-contrações podem ter nos MPP.…”
Section: Discussionunclassified
“…2 Exercícios que possam fortalecer o core e os MPP, como Pilates e Yoga, têm sido explorados como potenciais alternativas, mas os dados ainda são insuficientes. [47][48][49][50] De facto, Bø et al já tinha reportado uma taxa de IU nas professoras destas modalidades semelhante à da população geral, ainda que a maioria das participantes neste estudo praticava outras modalidades em simultâneo. 51 Num trabalho de 2018, a autora em conjunto com Kruger et al, concluiu que os MPP apenas contraiam 30% a 50% de uma contração em contexto de PFMT, durante a ativação de outros grupos musculares (como abdominais e glúteos), pelo que se questiona a eficácia terapêutica e o impacto que as co-contrações podem ter nos MPP.…”
Section: Discussionunclassified
“…To achieve the outcome, we would like to improve mindfulness training techniques which include sitting meditation, body scan, Hatha yoga, walking mediation as well as bladder and pelvic floor muscle training. These practices were conducted either alone or in combination with other interventions) [ 16 ]. The informal practices in this study were implemented through home-based practice using a CD with meditation instruction [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“… 3 Studies in almost every field of medicine examine yoga’s benefits ( Table 2 ). 4 , 5 , 6 , 7 , 8 , 9 The most studied disorders are in (1) mental health, (2) cardiovascular disease, and (3) respiratory disease. 3 …”
Section: Yogamentioning
confidence: 99%
“… 4 All 13 Cochrane reviews on yoga concluded that further, large-scale, methodological robust trials are required to establish evidence for yoga as a stand-alone treatment. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Accordingly, yoga should be used as a potent therapy in addition to standard care.…”
Section: Yogamentioning
confidence: 99%